Novel Dimer Derivatives of PF-543 as Potential Antitumor Agents for the Treatment of Non-Small Cell Lung Cancer - Su Bin Kim; Khem Raj Limbu; Yoon Sin Oh; Soo Lim Kim; Seung Ki Park; Dong Jae Baek; Eun-Young Park (MDPI AG, 2022)
Lung cancer can be divided into non-small cell lung cancer (NSCLC) and small cell lung cancer, and the incidence and mortality rate are continuously increasing. In many cases, lung cancer cannot be completely treated with surgery, so chemotherapy is used in parallel; however, the treatment often fails due to drug resistance. Therefore, it is necessary to develop a new therapeutic agent with a new target. The expression of sphingosine kinase promotes cancer cell growth and survival and induces resistance to chemotherapeutic agents. Sphingosine-1-phosphate (S1P), produced by sphingosine kinase (SK), has been shown to regulate cancer cell death and proliferation. PF-543, currently known as an SK inhibitor, has been reported to demonstrate low anticancer activity in several cancers. Therefore, in this study, a derivative of PF-543 capable of increasing anticancer activity was synthesized and its efficacy was evaluated by using an NSCLC cell line and xenograft animal model. Based on the cytotoxic activity of the synthesized compound on lung cancer cells, the piperidine forms (Compounds 2 and 4) were observed to exhibit superior anticancer activity than the pyrrolidine forms of the head group (Compounds 1 and 3). Compounds 2 and 4 showed inhibitory effects on SK1 and SK2 activity, and S1P produced by SK was reduced by both compounds. Compounds 2 and 4 demonstrated an increase in the cytotoxicity in the NSCLC cells through increased apoptosis. As a result of using an SK1 and SK2 siRNA model to determine whether the cytotoxic effects of Compounds 2 and 4 were due to SK1 and SK2 inhibition, it was found that the cytotoxic effect of the derivative was SK1 and SK2 dependent. The metabolic stability of Compounds 2 and 4 was superior compared to PF-543, and the xenograft experiment was performed using Compound 4, which had more excellent MS. Compound 4 demonstrated the inhibition of tumor formation. The results of this experiment suggest that the bulky tail structure of PF-543 derivatives is effective for mediating anticancer activity, and the results are expected to be applied to the treatment of NSCLC.